Die dogmatiese binding van die prediking - Dreyer, T. F. J. (Hervormde teologiese studies, 1985)
The confessional binding of preaching The preacher as an ordained minister of his church is bound by the church confessions. This confessional binding has a certain influence and restriction on his preaching. This research is an attempt to evaluate the influence of the confession of the church on the process of hermeneutical understanding and preaching.